Strategy of Khithabah in Dealing with Converts to Islam in Sarawak Malaysia - Nurul Amiranadira (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2018)
Activities of Islamic da’wah in Sarawak, Malaysia, especially among converts to Islam (muallaf) increased quite high, however, there are still converts who do not fully understand the teachings of Islam. One of the institutions that gives attention to preaching especially in khitabah (public speaking) for converts is Urusetia Saudara Kita (USK). With the limitations and obstacles encountered, USK took the initiative through its biblical strategy in increasing the understanding of converts. This study aims to determine the strategies, obstacles and how to deal with USK obstacles in the converts of Kuching, Sarawak, Malaysia. The results of research with this qualitative method found that converts in the area were divided into two groups namely, converts living in cities and converts living in villages. The converts living in the city are divided into three, namely, active, inactive and problematic converts. The preachers at USK used the implementation of different khithabah strategies to increase the understanding of the Islamic religion of the converts. Among the khithabah strategies undertaken by da'i at USK are mastery of languages, visiting and delivering material on creed, sharia and morals. Constraints faced include shortcomings, language difficulties, limited time, old age, remote location and limited equipment. USK tried to find the best way to overcome these obstacles properly.Kegiatan dakwah Islam di Sarawak, Malaysia khususnya di kalangan muallaf meningkat cukup tinggi, namun, masih terdapat muallaf yang belum memahami ajaran agama Islam dengan sepenuhnya. Salah satu lembaga yang memberikan perhatian dalam dakwah khususnya khitabah kepada muallaf adalah Urusetia Saudara Kita (USK). Dengan keterbatasan dan hambatan yang dihadapi, USK melakukan inisiatif melalui strategi khitabahnya dalam meningkatkan pemahaman para muallaf. Penelitian ini bertujuan untuk mengetahui strategi, hambatan serta  cara menghadapi hambatan USK di jamaah muallaf Kuching, Sarawak, Malaysia. Hasil penelitian dengan metode kualitatif ini menemukan bahwa muallaf di daerah tersebut terbagi kepada dua golongan yaitu, muallaf yang tinggal di kota dan muallaf yang tinggal di desa. Muallaf yang tinggal di kota terbagi kepada tiga yaitu, muallaf yang aktif, tidak aktif dan bermasalah. Para da’i di USK menggunakan penerapan strategi khithabah yang berbeda untuk meningkatkan pemahaman agama Islam para jamaah muallaf. Di antara strategi khithabah yang dilakukan da’i di USK adalah penguasaan bahasa, berkunjung dan menyampaikan materi tentang akidah, syariah dan akhlak. Hambatan yang dihadapi di antaranya Kekurangan da’i, kesulitan bahasa, keterbatasan waktu, usia mad’u yang sudah tua, lokasi yang jauh dan keterbatasan perlengkapan.  USK berusaha mencari jalan yang terbaik untuk menyelesaikan hambatan-hambatan tersebut dengan baik.